Laboratory of studies and practices in women's health: experience report (Research, Society and Development, 2021)
Objective: Relate an experience of developing a teaching project called the Laboratory of Studies and Practices in Women's Health. Methods: This is an experience report that describes the experiences from the insertion in activities in the teaching process of the discipline Nursing in Women's Health and Pediatric in Primary Care of the Nursing Course at a public university in southern Brazil. The meetings in the laboratory took place fortnightly, from August to December 2019. Results: To simulate care practice, realistic simulations were developed based on clinical cases related to women's health and roadmaps were built to guide nursing consultations. At the end, the students highlighted negative and positive points of the experience, discussing and reflecting on what could be modified and improved in the practice performed. The teaching-learning experience in the skills laboratory, through the teaching project, proved to be positive for students and teachers involved. This methodology provided moments of study that were relaxed, capable of reflection, and learning. Conclusion: Projects like this promote decision making, the strengthening of skills and the exercise of leadership, enabling greater confidence to develop essential skills and competencies in the work of nurses.